Sleep and quality of life in people with ileal conduit. (1st November 2016) - Cavdar, Ikbal; Temiz, Zeynep; Ozbas, Ayfer; Can, Gulbeyaz; Tarhan, Fatih; Findik, Ummu Yildiz; Kutlu, Fatma Yasemin; Akyuz, Nuray
Abstract: Objective: The aim of this study was to determine the sleep quality and the association between sleep quality and quality of life in people with ileal conduit. Materials and methods: A descriptive and cross-sectional design was adopted. The study sample comprised 111 people with ileal conduit operated on in urology clinics in a state hospital between January 2011 and May 2014. Six months after the operation, they were called by telephone to participate in the study. Data for the study were collected using a questionnaire form, the Pittsburgh Sleep Quality Index (PSQI) and the Stoma Quality of Life Scale (SQLS). Results: The mean ± SD total PSQI score of the people with ileal conduit was 10.20 ± 2.95, mean total score of SQLS was 43.63 ± 7.21, mean Work/Social Function domain score was 37.27 ± 5.80 and mean Stoma Function domain score was 50.0 ± 12.56. The total sleep quality had a low degree of negative correlation with total SQLS score, a medium degree of negative correlation with Work/Social Function ( r  = –0.327, p  < .001) and no correlation with Stoma Function ( r  = –0.096, p  > .001). People using a night drainage system had higher sleep quality. Conclusions: This study determined that quality of life and sleep deteriorate in people with ileal conduit. The quality of life decreases when the sleep quality is poor, and decreased quality of life affects quality of sleep in people with ileal conduit.